2009
DOI: 10.1002/adsc.200900665
|View full text |Cite
|
Sign up to set email alerts
|

A Coherent Mechanistic Rationale for Additive Effects and Autoinductive Behaviour in Proline‐Mediated Reactions

Abstract: Abstract. Differences in the kinetic behavior of aldol reactions compared to aminoxylation and amination reactions are rationalized by consideration of the ratedetermining step in each case. Both autoinductive behavior and the rate-enhancing effect of additives are attributed to an effect on the enamine formation step.Keywords: organocatalysis · kinetics · autoinduction · amino acid catalysis · reaction mechanism Proline catalysis, elegantly revived by List, Lerner and Barbas in 2000 [1], has demonstrated eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…All these discrepancies could mislead the interpretation for a simple nonlinear effect [141]. Finally, kinetic studies for this process demonstrated that it was characterized by well-behaved positive order kinetics, contrary to that observed in other related organocatalytic processes [142].…”
Section: Intermolecular Reaction Mechanismmentioning
confidence: 91%
“…All these discrepancies could mislead the interpretation for a simple nonlinear effect [141]. Finally, kinetic studies for this process demonstrated that it was characterized by well-behaved positive order kinetics, contrary to that observed in other related organocatalytic processes [142].…”
Section: Intermolecular Reaction Mechanismmentioning
confidence: 91%
“…56,29f It was concluded that the autoinduction occurs in these reactions but not in the aldol reaction because of a difference in the rate-determing steps. 57 …”
Section: Enamine/iminium Catalysismentioning
confidence: 99%
“…However, to promote specific reactions the application of dual or cooperative catalyst combinations [6] or the use of (co-catalytic) additives is slowly emerging because this often can prove beneficial for tuning both the reactivity and selectivity of existing catalytic systems. With respect to proline, additives [7][8][9] such as water, acids, or bases have successfully been shown to influence the outcome of the reactions and are already understood in part. [10] Even so, detailed experimental studies in solution, for example, with regards to the effect of additives on the reactive enamine intermediates, are rather scarce.…”
Section: Introductionmentioning
confidence: 99%